Development of PI Controller for Disc Speed - Mohd Amin, Nur Huda; Kasdirin, Hyreil Anuar; Md Nawawi, Mohamad Riduwan; Ab Ghani, Mohd Ruddin (2011)
This paper discuss about the development of Proportional and Integral (PI) controller for disc speed by involving the disturbance at the feedback control. The effect of the disturbance to the disc speed system is eliminated by Proportional and Integral (PI) controller. The PI controller is tuned heuristically from the MATLAB/simulink at which integrated with the disc plant. The performance of the disc plant is analyzed in real-time. Based on the analysis in real-time, this paper shows that the performance of the PI controller with disturbance and without disturbance. The result with disturbance shows that the output response quite closes to the result without disturbance even though the overshoot is about 8 percent. By the way, the rise time and settling time of the disc speed with disturbance is reduced for the time less than 0.01 and 0.95 seconds each. From the results with and without disturbance, this paper concludes that the development of PI controller for this speed in simulation give less error about 0.02 compared to the real-time system.